Investigations into Cytauxzoon felis among the domestic cat population of eastern Kansas - Wikander, Yvonne (Kansas State University, 2021)
Cytauxzoon felis is a tick-transmitted, obligate, hemoprotozoal, piroplasmid pathogen of felids and the causative agent of cytauxzoonosis. It has a complex life cycle which includes a tick as its definitive host and a felid as its intermediate host. Since its first description in 1976, C. felis infections of felids have been reported in several southeastern and south-central U.S. states, overlapping with the ranges of its two known biological vectors, Amblyomma americanum (Lone Star tick) and Dermacentor variabilis (American Dog tick). Infected felids demonstrate disease as either an acute, often-fatal, infection or a subclinical carrier infection. While statewide awareness and concern of C. felis infections have increased, few studies have evaluated the incidence of acute cytauxzoonosis, prevalence of carriers, and associated disease risk factors among domestic cats in endemic areas such as eastern Kansas. As such, the objective of this thesis was to investigate C. felis infections among the domestic cat population of eastern Kansas. Our first objective was to perform a retrospective review of Kansas State Veterinary Diagnostic Laboratory (KSVDL) feline records to identify: i) the incidence of acute cytauxzoonosis in Kansas over a 14-year period (2006-2019), and ii) risk factors associated with a diagnosis of acute cytauxzoonosis. The overall incidence trend was largely unchanged for the case review period and the feline risk factors most commonly associated with acute disease was >1-year old male owned cats’ samples submitted during the spring and summer. Felids that survive acute disease often remain infected and serve as reservoirs for subsequent tick transmission to other susceptible felines. Several states near Kansas (Arkansas, Oklahoma, Missouri) have identified C. felis-carrier domestic cat populations. Thus, the second objective of our study was to determine: i) the prevalence of C. felis-carriers in the domestic cat population in eastern Kansas using a quantitative PCR assay targeting the C. felis Cox3 mitochondrial gene, and ii) risk factors associated with cats that develop into C. felis carriers. An overall asymptomatic feline C. felis infection prevalence of 25.8% was determined in eastern Kansas with a seasonal fluctuation of more C. felis-survivors identified in spring and fall. Our study demonstrates that C. felis-domestic cat carriers are common among cats in eastern Kansas and suggests that more cats likely survive cytauxzoonosis than previously expected. Collectively, our studies present new information on the state of acute and carrier cytauxzoonosis cases among domestic cats in eastern Kansas. Investigating the incidence of acute cytauxzoonosis, patient risk factors, roles of domestic cat carriers, and ecological variables that influence disease transmission are important towards developing and communicating the need for effective cytauxzoonosis control strategies for high-risk cat populations, including recommending year-round use of acaricide products for all cats that spend any time outdoors. More studies are needed to further identify factors affecting C. felis and other Cytauxzoon spp. infections transmission, progression, and treatment options and outcomes within the U.S. and globally.
Keywords: Cytauxzoon felis; Domestic cat; Cytauxzoonosis; Acute disease; Chronic carrier; Tick-borne disease